2010
DOI: 10.1002/cctc.201000225
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Titanium Dioxide Phases in Mesostructured Silica Matrices with Photocatalytic Activity

Abstract: An imidazole type ionic liquid (IL), 1‐hexadecyl‐3‐methylimidazolium chloride (I16IL) was used as a template in the preparation of mesoporous silica with incorporated titanium dioxide. In this process, the IL is the structural template as well as the source of the Ti. The steps leading to the formation of the nanocrystalline metal oxide include: a) formation of metal‐containing IL (M‐IL); b) using the M‐IL as a template for the mesoporous silica; c) calcination of the sample to remove the organic moiety, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…This is owed to tunable solvent properties that can readily interact with various surfaces to facilitate the distribution of particles by in situ formation of metal oxide nanoparticles on the mesoporous supports. Gopala et al 119 demonstrated a facile method of introducing Ti centres into the mesoporous silica support by impregnation of an acidic solution of TiCl 4 mixed in N,N-dialkylimidazolium chloride type ILs such as 1-hexadecyl-3-methylimidazolium chloride. It forms a mesophase in aqueous solution with the TEOS precursor as well as interacts with the TiCl 4 to form an imidazole based chlorometalate complex, Ti-I 16 IL.…”
Section: Non-hydrolytic Methodsmentioning
confidence: 99%
“…This is owed to tunable solvent properties that can readily interact with various surfaces to facilitate the distribution of particles by in situ formation of metal oxide nanoparticles on the mesoporous supports. Gopala et al 119 demonstrated a facile method of introducing Ti centres into the mesoporous silica support by impregnation of an acidic solution of TiCl 4 mixed in N,N-dialkylimidazolium chloride type ILs such as 1-hexadecyl-3-methylimidazolium chloride. It forms a mesophase in aqueous solution with the TEOS precursor as well as interacts with the TiCl 4 to form an imidazole based chlorometalate complex, Ti-I 16 IL.…”
Section: Non-hydrolytic Methodsmentioning
confidence: 99%
“…The band gap energy of undoped TiO 2 was found to be 3.0 eV, which is in good agreement with the reported value for anatase TiO 2 (3.1-3.2 eV). 39,[48][49][50] Incorporation of U into the TiO 2 matrix leads to a narrower band gap, and the TiU3 sample has the lowest band gap energy (2.0 eV). These results show that a small amount of U-doping can signicantly modify the band gap structure of TiO 2.…”
Section: Dr-uv-vismentioning
confidence: 99%
“…It should be noted that [C 16 -mim]-based salts were previously used either as surfactants or as a part of the gel composites. In addition, the cetyl-containing, CO 2 H-functionalized imidazolium salt [N-C 16 ,N′-CO 2 H-im]­Br was used to gel a binary (H 2 O/DMSO) mixture at 20 wt %, whereas [C 16 -mim]­Br, which was used as a control, failed to induce the gelation . Furthermore, betaine-ester imidazolium bromide, that is, [C 1 ,(CH 2 CO 2 )­C 16 -im]Br (at 21.9–49.3 wt % concentration), was used for gelation of wet CHCl 3 ; the MGC for [C 1 ,(CH 2 CO 2 )­C 16 -im]­PF 6 and [C 1 ,(CH 2 CO 2 )­C 16 -im]­BF 4 salts was above 50 wt % .…”
Section: Introductionmentioning
confidence: 99%